2015
DOI: 10.1161/atvbaha.115.306475
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 Signaling Is Critically Required in Stromal Cells in Kawasaki Disease Vasculitis Mouse Model

Abstract: Objective Kawasaki disease (KD) is the most common cause of acute vasculitis and acquired cardiac disease among US children. We have previously shown that both TLR2/MyD88 and IL-1β signaling are required for the Lactobacillus casei cell wall extract (LCWE)-induced KD vasculitis mouse model. The objectives of this study were to investigate the cellular origins of IL-1 production, the role of CD11c+ Dendritic Cells (DCs) and macrophages and the relative contribution of hematopoietic and stromal cells for IL-1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
109
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 77 publications
10
109
0
1
Order By: Relevance
“…For the first time, we demonstrate that in addition to Il1b , disruption of Il1a or the use of IL-1α neutralizing antibody significantly inhibited LCWE-induced AAA formation, highlighting the critical role played by IL-1α, in addition to IL-1β in AAA formation in this vasculitis model. Indeed, we have also recently shown the non-overlapping roles for IL-1α and IL-1β in LCWE-induced coronary arteritis lesions 57 . Supporting these experimental findings, serum IL-1α levels are significantly correlated with AAA severity in human patients and surgical endovascular repair decreased the IL-1α levels 60 , further suggesting a role of IL-1α in human AAA formation as well.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…For the first time, we demonstrate that in addition to Il1b , disruption of Il1a or the use of IL-1α neutralizing antibody significantly inhibited LCWE-induced AAA formation, highlighting the critical role played by IL-1α, in addition to IL-1β in AAA formation in this vasculitis model. Indeed, we have also recently shown the non-overlapping roles for IL-1α and IL-1β in LCWE-induced coronary arteritis lesions 57 . Supporting these experimental findings, serum IL-1α levels are significantly correlated with AAA severity in human patients and surgical endovascular repair decreased the IL-1α levels 60 , further suggesting a role of IL-1α in human AAA formation as well.…”
Section: Discussionmentioning
confidence: 77%
“…We have previously shown that the caspase-1/IL-1α and IL-1β pathways are important for the development of coronary arteritis and myocarditis in the LCWE-induced KD murine model 25, 57 . In the current study, we found that IL-1/IL-1R signaling and both IL-1 α and IL-1β are critical for the formation of AAA, suggesting that the development of cardiovascular lesions associated with KD in both coronary artery and systemic arteries, including for AAA, may share a similar pathophysiology through the NLPR3 inflammasome and the IL-1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the LCWE-induced mouse model of KD vasculitis have shown that the NLRP3 inflammasome, caspase 1 activation and IL-1β and IL-1α are important in KD vasculitis (Rosenkranz, Schulte et al 2005, Lee, Schulte et al 2012, Lee, Wakita et al 2015). The IL-1 R antagonist, anakinra, which blocks both IL-1α and IL-1β, significantly blocked coronary arteritis, aortitis and myocarditis in this experimental model (Lee, Schulte et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [51] showed the critical role of IL-1 in the pathogenesis of KD using mice knockout models and antibodies. This then led to clinical trials for the use of IL-1R (Anakinra) in children with KD and is currently in phase IIa of clinical trials [52].…”
Section: Etiopathogenesismentioning
confidence: 99%